2015
DOI: 10.1093/jxb/erv263
|View full text |Cite
|
Sign up to set email alerts
|

A salt-regulated peptide derived from the CAP superfamily protein negatively regulates salt-stress tolerance inArabidopsis

Abstract: HighlightAn 11 aa peptide derived from one of the cysteine-rich secretory proteins, antigen 5, and pathogenesis-related 1 (CAP) superfamily is salt regulated, conferring salt susceptibility through suppression of salt-tolerance genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 53 publications
3
71
0
1
Order By: Relevance
“…This was recently investigated using the CNYx motif on PROAtCAPE1, the precursor protein for the AtCAPE1 peptide (Chien et al ., ). This study showed that a mutation of this CNY sequence can abolish the cleavage of the AtCAPE1 peptide (Chien et al ., ). Analysis of this peptide sequence shows that it appears conserved in most of the wheat TaPR‐1 proteins (Figure ) and falls within our proposed SnTox3–TaPR‐1 interaction surface.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This was recently investigated using the CNYx motif on PROAtCAPE1, the precursor protein for the AtCAPE1 peptide (Chien et al ., ). This study showed that a mutation of this CNY sequence can abolish the cleavage of the AtCAPE1 peptide (Chien et al ., ). Analysis of this peptide sequence shows that it appears conserved in most of the wheat TaPR‐1 proteins (Figure ) and falls within our proposed SnTox3–TaPR‐1 interaction surface.…”
Section: Discussionmentioning
confidence: 97%
“…It was speculated that the CNYx motif immediately upstream of CAPE1 is required for cleavage from PR-1b (Chen et al, 2014). This was recently investigated using the CNYx motif on PROAtCAPE1, the precursor protein for the AtCAPE1 peptide (Chien et al, 2015). This study showed that a mutation of this CNY sequence can abolish the cleavage of the AtCAPE1 peptide (Chien et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the tomato preproprotein PR1b was characterized by containing the PxGNxxxxxPY motif in the C-terminus. The CAP-derived peptide 1-like (CAPE1-like) of the C-terminal portion was discovered to have functions in induced immunity in the defense signaling as a novel damage-associated molecular pattern (Chen et al 2014;Chien et al 2015;Meijer et al 2019). Therefore, the exact biological function and bioactivity pathway of PR-1 proteins need to be further revealed, and in mulberry there is still little information related to PR1 genes.…”
Section: Introductionmentioning
confidence: 99%
“…For many years it was thought that tomato PR-1b encodes a 14-kD protein with antifungal activity (Niderman et al, 1995). Now it appears that it also encodes the CAPE1 peptide with antibacterial activity and antiherbivory activity and a role in the regulation of salt stress responses (Chen et al, 2014;Chien et al, 2015). At least 30 novel putative CAPE1-like peptides carrying the characteristic Pro-rich PxGNxxxxxPY motif were found in Solanoideae, Nicotianoideae, Viticeae, Brassicaceae, Fabaceae, and Poaceae (Chen et al, 2014) (Figure 3).…”
Section: Peptides Derived From a Functional Precursormentioning
confidence: 99%
“…It is suggested that CAPE1 may be a novel DAMP (damage-associated molecular pattern) for induction of immunity, similar to HYPSYS, RALF, and At-Pep1 (Pearce et al, 2001a(Pearce et al, , 2001bHuffaker et al, 2006;Albert, 2013;Trivilin et al, 2014). Recently, it was shown that At-CAPE1 functions as a negative regulator of salt stress (Chien et al, 2015).…”
Section: Peptides Derived From a Functional Precursormentioning
confidence: 99%